Fig 10 - - Limin Ma (556873) (2024)
The comparison between PET images reconstructed by different algorithms and the label images focuses on specific pixel profiles: (a) shows the pixel values along the 128th row of the corresponding images. (b) shows the pixel values along the 128th column of the corresponding images.